Building Information Modeling as a Moderator Effects the Relationship Between Sustainability Metrics and Stakeholder Satisfaction - Hisham Noori Hussain Al-Hashimy (Journal of Techniques)
The oil industry is, by virtue of being a resource of value addition, the engine of industrialisation in countries. When focusing on environmental concerns today, studying the connection between financial management and Building Information Modelling (BIM) in climate-friendly oil projects is highly recommended. This paper is dedicated to the role of sustainability and Iraq’s decisions in Accounting and Information Systems in Iraq’s oil sector. It aims to capture the relationship between everything that is based on sustainability metrics and economic actors who also play important roles in such undertakings. The research succeeded in collecting data by preparing a survey, which was conducted among leading oil companies in Iraq, with the aim of determining their information system procedures. The data was analysed using the methodology of Partial Least Squares Structural Equation Modelling (PLS-SEM). The results illustrate the positive help for BIM by including sustainability metrics. The information system type for the BIM also significantly influences the relationship between sustainability indicators and public sectors, with public sector participants being the more determinant group. This means that financial metrics, which may be interpreted as a performance factor for BIM, play a role in creating links that serve as the predicates of the sustainability indicators. Additionally, it rBIMes the concept of trade-off on the operational aspects between sustainability and economic gains in oil trading by adding a unique perspective to existing literature. The model created in this study is grounded on the PLS-SEM, complemented by the literature, and the hypotheses are tested. Through the inclusive coverage of the oil industry, the information can enlighten and guide effective strategies for collaborating with architectural work stakeholders that highlight the importance of oil sector proposals.